Sustainable innovation reporting and emerging technologies : promoting accountability through artificial intelligence, blockchain, and the internet of things - Maione, Gennaro (Emerald studies in sustainable innovation management, 2024)
At first glance, accountability and innovation seem to contradict one another. However, these seemingly opposing forces may complement one another in pursuing sustainable innovation reporting. Maione takes the reader on an enlightening journey structured around three central research questions: delving into the historical evolution of accounting, the challenges and opportunities in sustainable innovation reporting, and the potential collaborative paths for scholars and practitioners in the field. In such a conceptual exploration, Sustainable Innovation Reporting and Emerging Technologies stimulates thoughtful reflection and transformative action in accounting and sustainability. Advocating for a revised understanding of accounting that transcends its traditional role as a mere recorder of economic transactions, the book invites readers to engage with the evolving discourse on accountability and emerging technologies, offering a comprehensive and forward-thinking perspective. The Emerald Studies in Sustainable Innovation Management series aims to explore innovation management's advancements in turbulent times, with special attention to the transition towards a sustainable economy. Innovation management is evolving rapidly due to positive phenomena, such as digitalization and the green transition, and negative ones, such as crises and global emergencies.